Students’ Perception and Motivation on Hybrid Learning in English at 11th Grade Students of SMK Negeri 3 Padang - Annisa Turrahmah; Havid Ardi (Journal of English Language Teaching, 2022)
In the pandemic situation encourage several school modify their learning activities with combining online learning and offline learning. The combination of the online learning and face to face learning in the school is known as hybrid learning. The results of this analysis on the hybrid learning applied during the Covid-19 pandemic can be used as consideration for future policymaking. The purpose of this study is to identify students' perception on hybrid learning in English subject and to measure students' motivation on hybrid learning in English subject. This research used descriptive quantitative research. The sample for this research was 65 students of SMK 3 Padang. The data collection technique used in this research was a questionnaire. Therefore, the results of this study showed that the majority of SMK 3 students had a positive or good perception of the implementation of hybrid learning. The students agree that the use of hybrid learning motivates students to be more active in class, improves students’ critical thinking, interpretation, communication, collaboration skills.